Práticas arteterapêuticas com adolescentes residentes em um instituto federal - Ferro, Elaine (2024)
Art therapy is a field of professional practice based primarily on the principles of art and psychology. Using various forms of artistic expression, it aims to improve individuals' mental health and quality of life. This study investigates the application of art therapy practices with adolescents living in a Federal Institute, addressing topics such as change, identity, childhood memories, and interpersonal connections. The results highlight the transformative role of art therapy, which provides a safe space for creative expression, promotes self-knowledge, and strengthens both emotional resilience and social skills, promoting greater integration among young people.